Multiphoton, multimode state classification for nonlinear optical circuits - Kopylov, Denis A.; Offen, Christian; Ares, Laura; Wembe Moafo, Boris Edgar; Ober-Blöbaum, Sina; Meier, Torsten; Sharapova, Polina R.; Sperling, Jan (Physical Review Research)
We introduce a new classification of multimode states with a fixed number of photons. This classification is based on the factorizability of homogeneous multivariate polynomials and is invariant under unitary transformations. The classes physically correspond to field excitations in terms of single and multiple photons, each of which is in an arbitrary irreducible superposition of quantized modes. We further show how the transitions between classes are rendered possible by photon addition, photon subtraction, and photon-projection nonlinearities. We explicitly put forward a design for a multilayer interferometer in which the states for different classes can be generated with state-of-the-art experimental techniques. Limitations of the proposed designs are analyzed using the introduced classification, providing a benchmark for the robustness of certain states and classes.

Videobasierte Lehr-Lern-Settings entwickeln: Bildung für nachhaltige Entwicklung in der Kita als interdisziplinärer Lehr- und Lerngegenstand. Workshop am Tag der Lehre zum Thema: „Teaching for Future - Nachhaltige Lehre und Lehre über Nachhaltigkeit“. Universität Paderborn. - Büker, Petra; Göddertz, Nina; Glawe, Katrin; Reichenbach, Alexandra; Wagner, Melanie

Starting early or late? Parental perspectives on the onset of English language education at primary school in Germany - Rumlich, Dominik; Porsch, Raphaela (Early language education in instructed contexts)
Abstract This study investigates parents’ perspectives on the preferred onset of English education in Germany and potential explanatory factors drawing on a cross-sectional survey of 2,645 parents from the EUBE project ( E nglisch u nterrichts b eginn aus E lternsicht / Parental perspectives on the onset of English Language Education). Results reveal that a significant majority of parents advocate for an early start in year 1 or 2 of primary school, generally aligning with their strong conviction of the importance of English, high educational aspirations and expectations, and their own (early) start of language education. The findings contribute to a deeper understanding of parental perspectives that have also shown to be related to multiple indicators of educational success in general and achievements in language learning in particular.

Das Lehr‑/Lernkonzept inklud‐e: Durch videobasierte Fallarbeit Studierende des Grundschullehramtes für Inklusion sensibilisieren - Herding, Jana; Glawe, Katrin; Caci, Stefania Vita; Büker, Petra (Diskurse und Praktiken der Heterogenität)

PrimOER: Professionalisierung der Grundschullehrkräftebildung durch eine neue „Kultur des Teilens“ in der Lehre. Posterbeitrag auf der 33. Jahrestagung der DGfE-Kommission Grundschulforschung und Pädagogik der Primarstufe an der PH Vorarlberg, Österreich. - Büker, Petra; Kamin, Anna-Maria; Oevel, Gudrun; Bernasconi, Bernadette; Löwen, Jana; Bruhnke, Lorena; Knurr, Moritz

Wege entstehen beim Gehen. Demokratiebildung in der Grundschule. - Büker, Petra; Knapp, Damaris; Schönknecht, Gudrun (Grundschulzeitschrift)

Grundschulforschung braucht Transfer: Brückenschläge zur Lehrkräftebildung, Bildungspolitik und Schulpraxis. Beitrag auf der 33. Jahrestagung der DGfE-Kommission Grundschulforschung und Pädagogik der Primarstufe an der PH Vorarlberg, Österreich. - Büker, Petra

Demokratie kann man lernen (Die Grundschulzeitschrift Jahresheft)

The Question of Methodology in Critical Political Economy of Communication and the Media - Fuchs, Christian (Journal of Communication Inquiry)
Critical political economy of communication and the media (CPECM) is an approach and field of study that critically analyzes how the interaction of politics and the economy in society shapes and is shaped by (mediated) communication. This study asks: What is the role of methodology in the approach of CPECM? How are methods and media ethics related in the critical study of media, economy, and society? The article argues that CPECM is distinct in that it asks special types of questions that are different from the questions asked by administrative research. This study points out 10 methodological dimensions of CPECM. It argues that empirical ideology critique should not be situated outside but inside of CPECM. It becomes evident that, other than conventional methods in media and communication studies, CPECM methodology is guided by ethics, moral philosophy, and critical theories.

DigiLex — A Checklist for the Evaluation of Digital Tools for Second and Foreign Language Lexical Learning - Lehmkuhl, Paulina; Wagner, Benedikt; Frisch, Stefanie; Rumlich, Dominik; Visser, Judith (TESOL Journal)
ABSTRACT The use of digital tools for second and foreign language lexical learning is increasingly popular and research in this area is constantly expanding. However, little has been written about specific criteria that could be used to identify tools with high‐quality lexical input, as available checklists and frameworks for digital media tend to neglect detailed analyses of the vocabulary domain. This article addresses this issue by presenting the Checklist for Evaluating Digital Resources for Lexical Learning (DigiLex), which combines important digital language learning criteria with an extensive evaluation of lexical content. The checklist is both theory‐based and user‐friendly, aiming to fill a gap between theory and practice in the field of digital lexical learning. The article discusses the theoretical basis of the checklist and integrates the results of a small pilot study with pre‐service and in‐service teachers, emphasizing feasibility in everyday learning and teaching. By providing an easy‐to‐use tool for identifying suitable digital resources, the DigiLex checklist aims to support language learners and teachers in self‐regulated lexical learning.

Kompetenzen für den erfolgreichen Übergang von der Sekundarstufe I in die berufliche Ausbildung sichern. Gutachten der Ständigen Wissenschaftlichen Kommission der Kultusministerkonferenz - Becker-Mrotzek, Michael; Efing, Christian; Gerick, Julia; Greefrath, Gilbert; Hammann, Marcus; Hannover, Bettina; Heckhausen, Jutta; Jost, Jörg; Keller, Stefan; Leiß, Dominik; Leutner, Detlev; Lewalter, Doris; et al.

Maximizing linguistic and cognitive potential: the role of vocal training with pop songs in teaching English as a foreign language - Vivone, Antonio; Rumlich, Dominik; Lehmann-Wermser, Andreas (Learning: Research and Practice)

High Voltage (5Vpp) Driver Monolithically Integrated with Thermally Tunable Optical Ring Resonators in a Silicon Photonics Technology - Weizel, Maxim; Gudyriev, Sergiy; Zazzi, Andrea; Müller, Juliana; Schwabe, Tobias; Witzens, Jeremy; Scheytt, J. Christoph (2025 32nd IEEE International Conference on Electronics, Circuits and Systems (ICECS))

Analogiebildung in kontextorientierten Lernumgebungen - Wedekind, Lisa; Pollmeier, Pascal; Fechner, Sabine (Entdecken, lehren und forschen im Schülerlabor)

CLIL-related benefits for general EFL proficiency - Rumlich, Dominik (The Cambridge Handbook of multilingual education)

Inspirationspapier: Digitale Kompetenzen fördern, Digital Divide überwinden – Was wir von Tschechien lernen können - Eickelmann, Birgit; Puchta, J.; Thieme, L.; Zöller, K.

Explainable Benchmarking through the Lense of Concept Learning - Zhang, Quannian; Röder, Michael; Srivastava, Nikit; Kouagou, N'Dah Jean; Ngonga Ngomo, Axel-Cyrille (Proceedings of the Knowledge Capture Conference 2025)

Jakob Wüest: Une histoire des connecteurs logiques. Causalité, argumentation, conséquence, finalité et concession. Tübingen: Narr / Francke / Attempto 2023, 319 S. (Tübinger Beiträge zur Linguistik, 586) - Kunert, Irene Dorothea (Romanische Forschungen)

Predetection squeezing as a resource for high-dimensional Bell-state measurements - Bianchi, Luca; Marconi, Carlo; Sperling, Jan; Bacco, Davide (Physical Review Research)
Bell measurements, entailing the projection onto one of the Bell states, play a key role in quantum information and communication, where the outcome of a variety of protocols crucially depends on the success probability of such measurements. Although in the case of qubit systems, Bell measurements can be implemented using only linear optical components, the same result is no longer true for qudits, where at least the use of ancillary photons is required. In order to circumvent this limitation, one possibility is to introduce nonlinear effects. In this work, we adopt the latter approach and propose a scalable Bell measurement scheme for high-dimensional states, exploiting multiple squeezer devices applied to a linear optical circuit for discriminating the different Bell states. Our approach does not require ancillary photons, is not limited by the dimension of the quantum states, and is experimentally scalable, thus paving the way toward the realization of an effective high-dimensional Bell measurement.

Sportsoziologie - Riedl, Lars (Sportwissenschaft. Themenfelder, Theorien und Methoden)